MISSION OVER ADAPTABILITY: HOW CULTURE AND ENVIRONMENT JOINTLY DRIVE PERFORMANCE IN TRADITIONAL SMES - Natsir, Uhud Darmawan (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
Purpose: This study investigates the direct and interactive effects of organizational culture and the physical-psychosocial work environment on employee performance within small and medium-sized enterprises (SMEs), specifically in the traditional brick-making industry in Takalar Regency, Indonesia. Design/methodology/approach: A quantitative approach was employed using a cross-sectional survey. Data were collected from 150 employees across 20 brick-making units through structured questionnaires measuring organizational culture (adaptability, consistency, mission, involvement), work environment (safety, equipment, peer support), and performance (task, contextual). Data analysis used Structural Equation Modeling (SEM-PLS) to test the hypotheses. Findings: The results indicate that both organizational culture and work environment have significant positive effects on employee performance. Furthermore, a positive organizational culture was found to strengthen the positive impact of a conducive work environment on performance. The